Comparative analysis of central corneal thickness in ocular hypertension and healthy individuals - Yu Zhang (Photodiagnosis and Photodynamic Therapy, 2024)
Objective: This study aimed to compare the central corneal thickness (CCT) between patients with ocular hypertension (OHT) and healthy individuals, and to investigate the relationship between CCT and intraocular pressure (IOP), diopter, and corneal endothelium cell count (CECC). Methods: The CCT of 30 healthy subjects and 38 patients with OHT was measured using a non-contact specular microscope. IOP, diopter, and CECC were also assessed for all participants. Comparative analysis of CCT between the two groups was performed, along with correlation analysis between CCT and each parameter. Results: The average CCT for all participants was 527.57 ± 35.84 µm. The average CCT was 516.07 ± 34.76 µm for healthy subjects and 536.66 ± 34.46 µm for patients with ocular hypertension, showing a significant difference between the two groups (P ≤ 0.05). CCT was not correlated with age (Pearson r = -0.098, P = 0.426), diopter (spherical equivalent refraction) (Pearson r = -0.158, P = 0.197), or corneal endothelium cell count (Pearson r = 0.065, P = 0.598). However, a positive correlation was found between ocular hypertension and central corneal thickness (Pearson r = 0.278, P = 0.022). Conclusion: Patients with ocular hypertension of members of the Chinese Han population exhibited greater CCT compared to healthy subjects in this study. CCT showed no association with age, diopter, or corneal endothelium cell count; however, a positive correlation was observed between intraocular pressure and CCT. With CCT as the abscissa and IOP as the ordinate, the linear regression equation is Y = 0.05+0.021X (F = 5.508, P = 0.022). The use of non-contact tonometers for measuring CCT may impact the accuracy of diagnosing and treating glaucoma and ocular hypertension.